Collaboration of community hospital endosonographers improves diagnostic yield of endoscopic ultrasonography guided tissue acquisition of solid pancreatic lesions - Quispel, Rutger (Endosc Int Open, 2019)
Background and study aims  Endoscopic ultrasound (EUS)-guided tissue acquisition (TA) is the method of choice for establishing a pathological diagnosis of solid pancreatic lesions. Data on quality and yield of EUS-guided TA performed in community hospitals are lacking. A study was performed to determine and improve the diagnostic yield of EUS-guided TA in a group of community hospitals. Methods  Following analysis of the last 20 EUS-guided TA procedures of solid pancreatic lesions performed in each of four community hospitals, a collaborative EUS interest group was formed and a prospective registry was started. During meetings of the interest group, feedback on results per center were provided and strategies for improvement were discussed. Results  In the BEFORE team formation cohort, 80 procedures were performed in 66 patients. In the AFTER team formation cohort, 133 procedures were performed in 125 patients. After team formation, the rate of adequate sample increased from 80 % (95 %CI [0.7 – 0.9]) to 95 % (95 %CI [0.9 – 1.0]) , diagnostic yield of malignancy improved from 28 % (95 %CI [0.2 – 0.4]) to 64 % (95 % CI [0.6 – 0.7]), and sensitivity of malignancy improved from 63 % (95 %CI [0.4 – 0.8]) to 84 % (95 %CI [0.8 – 0.9]). Multivariate regression analysis revealed team formation to be the only variable significantly associated with an increased rate of adequate sample. Conclusions  Formation of a regional EUS interest group with regular feedback on results per center, and discussions on methods and techniques used, significantly improved the outcome of EUS-guided TA procedures in patients with solid pancreatic lesions in community hospitals.